2012
DOI: 10.6002/ect.2012.0087
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Follow-Up of Treatment With Once-Daily Tacrolimus in De Novo Renal Transplant

Abstract: Patients taking tacrolimus QD tended to have lower trough levels and require higher dosages than those taking tacrolimus BID during the early posttransplant period, though the differences decreased with increasing time after transplant. Tacrolimus QD can be administered with excellent efficacy and safety in de novo renal transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Several studies revealed that TAC-OD required higher daily doses up to six months after transplantation than those on TAC-BID [2,13,14]. Kitada et al showed that recipients on TAC-OD therapy have lower tacrolimus blood concentration and necessitate to be administered higher doses than those receiving TAC-BID in the early posttransplant phase [15]. Our outcomes on daily dosage were consistent with previous studies; recipients having TAC-OD immunosuppressive therapy needed higher doses than those receiving TAC-BID.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Several studies revealed that TAC-OD required higher daily doses up to six months after transplantation than those on TAC-BID [2,13,14]. Kitada et al showed that recipients on TAC-OD therapy have lower tacrolimus blood concentration and necessitate to be administered higher doses than those receiving TAC-BID in the early posttransplant phase [15]. Our outcomes on daily dosage were consistent with previous studies; recipients having TAC-OD immunosuppressive therapy needed higher doses than those receiving TAC-BID.…”
Section: Discussionsupporting
confidence: 89%
“…Tacrolimus is principally absorbed from the intestines. The inactive components inserted into the capsule covering the active drug form create disparity among once-daily and twice-daily forms [14,15]. This prolonged-release period may be linked with problems in optimizing the blood concentration in the target concentration through the initial post-transplant period.…”
Section: Discussionmentioning
confidence: 99%
“…According to de novo studies on Tac-OD, excellent survival rates and comparable safety profiles have been achieved with both formulations [4,5].…”
mentioning
confidence: 86%
“…ration during 3-12 months aft er transplantation [23]. On the contrary, Kitada et al demonstrated signifi cant diff erences in Tac daily dose between examined preparations in the early period aft er Tx (up to three months), which was not followed by the same trend at the end of the fi rst year [24].…”
Section: Volume 6 • Number 2 • August 2019 • Hophmentioning
confidence: 92%